Prevention of Tinea Corporis in Collegiate Wrestlers - Hand, James W. (1999)
OBJECTIVE: To examine the role of a comprehensive skin disease prevention protocol in conjunction with the use of a barrier cream to prevent tinea corporis (ringworm) in collegiate wrestlers. DESIGN AND SETTING: We studied a college wrestling team for 16 weeks during 1 season. During the first 8 weeks, no preventive measures were taken. For the remaining 8 weeks, wrestlers were randomized into 2 groups and used either a barrier or a placebo. SUBJECTS: Twenty-two male college wrestlers with a mean age of 20.4 years (range, 18.1 to 23.2), a mean weight of 68.4 kg (range, 55.8 to 130.2), and a mean height of 177.8 cm (range, 168.7 to 186.9). MEASUREMENTS: We performed skin checks daily. All new or exacerbated lesions were clinically diagnosed by the same team physician and recorded. RESULTS: Cases of tinea corporis declined from 10 diagnosed before initiation of the protocol to 1 after the protocol was initiated. One athlete in the placebo group was found to have tinea corporis versus none in the barrier cream group. CONCLUSIONS: Strict adherence to the prevention protocol for skin infections significantly decreased the number of cases of tinea corporis. The use of the barrier cream in conjunction with the prevention protocol did not result in any further statistical reduction in the number of wrestlers who contracted tinea corporis.